The Use of Coronary CT Angiography vs. Functional Stress Testing for Diagnosis of Stable Coronary Artery Disease- A Systematic Review and Meta- Analysis - Mahmood, Arhum; Mudassar, Hammad; Khalid, Haseeba; Khan, Faisal; Hack, Sarah; Mirza, Muhammad Sohail S.; Ali, Mohammed Abdul Muhaimin; Singla, Shivam; Singla, Bhavna (Cardiology and Cardiovascular Medicine, 2025)
Background: Coronary computed tomography angiography (CCTA) visualizes coronary artery anatomy, whilst useful stress testing assesses inducible cardiac ischemia. Although CCTA demonstrates higher diagnostic accuracy for coronary artery disorder (CAD) in comparison to functional testing, when using invasive coronary angiography as the reference standard, its effect on clinical outcomes remains uncertain. Objective: This systematic evaluation and meta-evaluation aimed to compare CCTA and functional stress testing in patients with stable coronary artery disease, focusing on the major adverse cardiac events (MACE), myocardial infarction (MI), revascularization, and cardiac hospitalization. Methods: A systematic seek of PubMed, MEDLINE, Cochrane Library, and Google Scholar databases diagnosed randomized controlled trials (RCTs) published between January 2016 and January 2025. Studies have been conducted in the event that they compared CCTA with useful stress testing in grownup patients with suspected CAD and reported patient results over at least one month of follow-up. Statistical analyses were carried out the use of random-consequences models, and heterogeneity was assessed the use of I² statistics. Results: Nine RCTs comprising 4,912 participants were included. For MACE, the pooled danger ratio (RR) turned into 0.92 (95% CI: 0.60– 1.40, *p* = 0.69, I² = 48%), indicating no enormous distinction between CCTA and functional testing. Similarly, no vast distinction changed into found for MI (RR: 0.74, 95% CI: 0.27–2.04, *p* = 0.55, I² = 60%), revascularization (RR: 1.40, 95% CI: 0.49–3.99, *p* = 0.53, I² = 62%), or cardiac hospitalization (RR: 0.91, 95% CI: 0.68–1.22, *p* = 0.53, I² = 0%). Conclusion: This meta-analysis found no good-sized distinction between CCTA and practical stress testing in lowering MACE, MI, revascularization, or cardiac hospitalization fees in patients with stable CAD. While CCTA gives anatomical elements and diagnostic accuracy, these advantages might not translate into advanced medical results compared to purposeful checking out. Further studies are needed to clarify the role of CCTA in guiding management techniques for strong CAD.